Kako varni so pogoji za učenje kajtanja v nekaterih slovenskih šolah? - Žavbi, Andraž (Šport (Ljubljana), 2018)
The aim of this paper was to determine how safe were some conditions for learning kitesurfing in some Slovenian schools, according to the IKO safety standard. The research was carried out in five (out of 14 operating, which represents a 35.7% sample of all operating schools) randomly selected Slovene kitesurfing schools, which operated in different locations in 2015 and 2016. We used a survey questionnaire that included two groups of variables 1.) IKO safety standard for schools (7 variables); 2.) IKO safety standard for instructors (8 variables). Data were obtained through guided surveys and by observing the implementation of courses in randomly selected schools. The evaluations in the form of 15 variables were evaluated by the instructors on the threestage Likert scale. We used Microsoft Excel to process data. We calculated the frequencies and presented them in the, according to the IKO safety standard in most of the requirements, were appropriate. Nevertheless, we have proposed some measures that can improve the safety of the participants. Considering that in Slovenia it is not possible to acquire adequate professional skills for work in the field of kitesurfing, we suggest that such training shold be organized as soon as possible with the appropriate professional organization.
Keywords: IKO; izboljšave; kajtanje; pogoji; pomanjkljivosti; šole; učenje; varnost; vodni športi